Examination of miners' immune response to coal dust and their quality of life - Biljana Mijović; Bojan Joksimović; Zlatko Maksimović; Slobodan Stanić; Milena Božinović; Radmila Balaban Đurević; Biljana Čančar (Биомедицинска истраживања, 2021)
Introduction: Inhalation of coal dust during blasting in brown coal mines has been shown to lead to a lung disease called pneumoconiosis. There is very little data in the literature on the direct impact of coal on the quality of life of people who work in coal mines as well as the body's immune response to the effects of coal dust. The aim was to examine the immune response to exposure to coal dust in miners in a brown coal mine and whether mine workers have poorer quality of life compared to those not exposed to coal dust. Methods: This is a cross-sectional study among 100 employees in the Brown Coal Mine in Ugljevik, of which 50 of them are exposed to coal dust on a daily basis. Blood samples were taken from all subjects to test for the presence of cytokines IL-2, 4, 5, 9, 10, 13, 17A, 17F, 21, 22, IFN-g and TNF-a. The quality of life of employees was measured using a questionnaire for self-assessment of physical and mental health (36-item Short-Form Health Survey, SF-36). Results: Group of miners had a significantly (p<0.05) higher concentrations of pro-inflammatory cytokines IL-6, IFN-g, IL-17A and IL-22 when compared to the control group. Subjects from the control group had significantly (p<0.05) higher concentrations of anti-inflammatory cytokines IL-4 and IL-10 when compared to the group of miners. The quality of life was significantly (p<0.05) better in the control group when compared to the group of miners. Conclusion: Physical functioning, general health, mental health and Physical component summary were significantly poorer in the group of miners. Exposition to coal dust led to a significant increase in the production of pro-inflammatory cytokines and a decrease in the production of anti-inflammatory cytokines.
Keywords: immune response; cytokines; coal dust